Distributed Small-Step Path Planning and Detection Method for Post-earthquake Robot to Inspect and Evaluate Building Damage - Tang, Zhaojia; Wang, Ping; Wang, Yong; Wang, Changgeng; Han, Yu (Frontiers in Neurorobotics, 2022)
Post-earthquake robot can be used extensively to inspect and evaluate building damage for safety assessment. However, the surrounding environment and path for such robot are complex and unstable with unexpected obstacles. Thus, path planning for such robot is crucial to guarantee satisfactory inspection and evaluation while approaching the ideal position. To achieve this goal, we proposed a distributed small-step path planning method using modified reinforcement learning (MRL). Limited distance and 12 directions were gridly refined for the robot to move around. The small moving step ensures the path planning to be optimal in a neighbouring safe region. MRL updates the direction and adjusts the path to avoid unknown disturbance. After finding the best inspection angle, the camera on the robot can capture the picture clearly, thereby improving the detection capability. Furthermore, the corner point detection method of buildings was improved using the Harris algorithm to enhance the detection accuracy. An experimental simulation platform was established to verify the designed robot, path planning method, and overall detection performance. Based on the proposed evaluation index, the post-earthquake building damage was inspected with high accuracy of up to 98%, i.e., 20% higher than traditional unplanned detection . The proposed robot can be used to explore unknown environments, especially in hazardous conditions unsuitable for humans.